Traffic incident and disaster management in the Netherlands - John Steenbruggen; Peter Nijkamp; Jan M. Smits; Ghaitrie Mohabir (Netcom)
Disaster Management and Traffic Incident Management involves the coordinated interactions of many public and private actors. On many levels, there is clearly a strong relation between the road infrastructure and the effective handling of large scale disasters. To support these tasks in an effective way, netcentric information systems are increasingly being seen as an important constraint to improve the cooperation between different emergency services. However, in the field of information systems there are many challenges and obstacles. Information, communication and coordination tasks, and especially problems in information quality, are identified as the main hurdles. This paper addresses, from a broad perspective, the relation and challenges between the two related fields.